Enhanced stability and photovoltage for inverted perovskite solar cells via precursor engineering. Issue 26 (17th June 2019) - Liu, Changwen; Kong, Weiguang; Li, Wang; Chen, Hong; Li, Dedi; Wang, Weijun; Xu, Baomin; Cheng, Chun; Jen, Alex K. Y.
Abstract : Precursor engineering toward enhanced V oc and stability of inverted perovskite solar cells with a champion power conversion efficiency of 20.7%. Abstract : We report on a method of precursor engineering to prepare high quality and stable perovskites based on formamidinium/methylammonium (FAMA) mixed-cations. CsI is commonly used to inhibit the photoinactive phase in FAMA perovskites. However, the hydrophilic nature of CsI would result in a structural instability issue at high relative humidity (RH). Besides, in inverted perovskite solar cells (PSCs) based on organic hole transport layers, the low conduction band minimum (CBM) of FAMA perovskites would lead to small open circuit voltage ( V oc ) (∼1.0 V), and thus additional surface passivation/modification layers are normally employed, indicating that it is essential to improve the basic precursors for high quality perovskite films. Herein, the proposed method is realized via ternary precursor alloying which endows the perovskite with increased grain size, enhanced crystallinity, reduced trap states, and a pure photoactive phase without the assistance of CsI. Without passivation/modification layers, the device V oc is enhanced markedly from 1.0 V to 1.1 V on average, and a champion power conversion efficiency of 20.7% with negligible hysteresis is achieved. Moreover, as they are free of hydrophilic CsI, both the photoactive perovskite films and devices exhibit excellent stability in ambient air. At high RH (70%), the optimized device without encapsulation only loses 16% of its efficiency after 1000 h storage, indicating the potential for the development of efficient and stable PSCs.